Unique case of trifurcation of the brachial artery: Its clinical significance - ÖZDOĞMUŞ, NECMETTİN ÖMER (WILEY-LISS, 2002)
The variability of the arteries in the upper extremity is considerable. This case is a report of a trifurcation of the brachial artery that divided into radial, ulnar, and superior ulnar collateral arteries high in the arm; the length of the brachial artery was only 4.9 cm. Because the upper extremity is a frequent site of injury, various surgical and invasive procedures are performed in this region: consequently, it is of utmost importance to be aware of arterial variations. For some medical procedures, there may be an increased ask of complications because of variant vessels; however, for other procedures, they may be beneficial. In addition to presenting a detailed anatomic study of the case. the clinical significance of the variation has been addressed. Clin. Anat. 15:224-227, 2002. (C) 2002 Wiley-Liss, Inc.
Keywords: ulnar artery; radial artery; superior ulnar collateral artery; variation; SUPERFICIAL ULNAR ARTERY; FLAP; FOREARM; NERVE; PATTERN; MUSCLES; ANATOMY